2019
DOI: 10.18502/npt.v6i4.1941
|View full text |Cite
|
Sign up to set email alerts
|

Immersing in problems: Challenges of women living with the husband on hemodialysis

Abstract: Background & Aim: The caregivers of hemodialysis patients experience a heavy caregiving burden. More caregiving pressure and burden have been reported of the women than men insofar as they are encountered with more physical and psychological problems. This paper explores the challenges faced by women living with husband on hemodialysis. Methods & Materials: The study followed a conventional content analysis method. The participants were selected through a purposive sampling method in hospitals of Shahi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These requirements increase patients' dependence on family caregivers, who are crucial for the provision of care and support [12]. As a consequence, family caregivers have to readapt their personal, family, social and labour activities to fit the demands of ESRD care [7,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These requirements increase patients' dependence on family caregivers, who are crucial for the provision of care and support [12]. As a consequence, family caregivers have to readapt their personal, family, social and labour activities to fit the demands of ESRD care [7,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, haemodialysis (HD) is the most common form of treatment (2)(3)(4). Although it allows patients to extend their life expectancy (5), this treatment is highly complex and requires several restrictions and life readjustments, not only for the patients but also for their family members (1,4,6,7). Patients need to adhere to a restrictive diet and fluid intake (6,8) and regularly attend to dialysis centres or consultations, hospitals, and clinics, and take different medications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its strict regime of attendance (3-4 times a week, with each session lasting up to 4 fours), HD can easily become a routinised activity that does not consider the psychological distress it causes on patients and families. However, several studies have shown that patients with ESRD undergoing HD may experience severe stress (7), anxiety (10), fear (11)(12)(13) and uncertainty about the future (14,15). A recent study found that most patients with this condition lived in fear of the disease and were scared about their future as they felt dependent on dialysis and could not survive without it (16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations